Isolation of antithrombin protein from local leeches (hirudinaria manillensis) - Abdul Latif, Fazilah (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1994)
Hirudinaria manillensis is a buffalo leech widespread in tropical parts of Asia. It is the same family as the European medicinal leech (Hirudo medicinalis) which has been used extensively in studying antithrombin protein called Hirudin. The purpose of this study is to isolate and purify antithrombin protein of â€œhirudin-likeâ€ protein from local leeches (Hirudinaria manillensis). From this study we found that the Rotofer cell (Isoelectric focussing cell) brought about a significance purification of antithrombin protein from local leeches in a minimum number of steps.